Hepatitis E Virus Infection Among Solid Organ Transplant Recipients at a North American Transplant Center. (18th January 2016) - Sue, Paul K.; Pisanic, Nora; Heaney, Christopher D.; Forman, Michael; Valsamakis, Alexandra; Jackson, Annette M.; Ticehurst, John R.; Montgomery, Robert A.; Schwarz, Kathleen B.; Nelson, Kenrad E.; Karnsakul, Wikrom
Abstract: Background.  Autochthonous hepatitis E virus (HEV) infection has been reported in over 200 solid organ transplant (SOT) recipients since 2006, yet little is known about the burden of HEV among SOT recipients in North America. We performed a retrospective, cross-sectional study to investigate the prevalence and risk factors associated with HEV infection among SOT recipients at our institution. Methods.  Children and adults (n = 311) who received allografts between 1988 and 2012 at the Johns Hopkins Hospital were assessed for evidence of HEV infection by testing posttransplantation serum samples for HEV antibody by enzyme immunoassay and HEV RNA by reverse transcription quantitative polymerase chain reaction. Individuals with evidence of posttransplant HEV infection (presence of anti-HEV immunoglobulin [Ig]M antibody, anti-HEV IgG seroconversion, or HEV RNA) were compared with individuals without evidence of infection and assessed for risk factors associated with infection. Results.  Twelve individuals (4%) developed posttransplant HEV infection. Posttransplant HEV infection was associated with an increased risk for graft rejection (odds ratio, 14.2; P = .03). No individuals developed chronic infection. Conclusions.  Solid organ transplant recipients in the United States are at risk for posttransplant HEV infection. Further studies are needed to characterize environmental risk factors and the risk of HEV infection after SOT in North America.